Pose estimation for health data analysis: advancing AI in neuroscience and psychology - Yu, Juan; Zhu, Daoyu (Frontiers in Neurology, 2025)
IntroductionThe integration of artificial intelligence (AI) with health data analysis offers unprecedented opportunities to advance research in neuroscience and psychology, particularly in extracting meaningful patterns from complex, heterogeneous, and high-dimensional datasets. Traditional methods often struggle with the dynamic and multi-modal nature of health data, which includes electronic health records, wearable sensor data, and imaging modalities. These methods face challenges in scalability, interpretability, and their ability to incorporate domain-specific knowledge into analytical pipelines, limiting their utility in practical applications.MethodsTo address these gaps, we propose a novel approach combining the Dynamic Medical Graph Framework (DMGF) and the Attention-Guided Optimization Strategy (AGOS). DMGF leverages graph-based representations to capture the temporal and structural relationships within health datasets, enabling robust modeling of disease progression and patient interactions. The framework integrates multi-modal data sources and applies temporal graph convolutional networks, ensuring both scalability and adaptability to diverse tasks. AGOS complements this by embedding domain-specific constraints and employing attention mechanisms to prioritize critical features, ensuring clinically interpretable and ethically aligned decisions.Results and discussionTogether, these innovations provide a unified, scalable, and interpretable pipeline for tasks such as disease prediction, treatment optimization, and public health monitoring. Empirical evaluations demonstrate superior performance over existing methods, with enhanced interpretability and alignment with clinical principles. This work represents a step forward in leveraging AI to address the complexities of health data in neuroscience and psychology, advancing both research and clinical applications.